From Threads to Frames: Animating an Immigrant Senior’s COVID-19 Pandemic Experience - Hung, Annie; Lin, Ching-Chiu; Zhang, Joan (Art/Research International)

(untitled) (University of Alberta, 2024)
Senior immigrants hold a wealth of experience and knowledge often unrecognized due to language and cultural barriers. This article promotes a collaborative approach within arts-based research (ABR) that flattens conventional hierarchies, creating a space where voices of participants and researchers are valued and heard. By embracing translation as both a method and metaphor in the co-creative research process, this article amplifies a senior immigrant’s unique response to the COVID-19 pandemic through her creative making. In this collaborative model, ABR actively involves a senior as co-researcher, building research on her local knowledge and insights. Our approach invites a reconsideration of social support strategies for immigrant seniors, advancing public discourse about their role and resilience within the arts education community.